Naskh in the Qur’ān: A Theoritical Review - Kusmana Kusmana (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2013)
This article deals with the theoretical dimension of naskh, discussing the term (in all of its various forms) from the standpoints of linguistic usage, literary context and conceptual framework. In addition, the article will discuss also the subject matter according to three figures: Tabarī, Tabarsī, and Zamakhsharī with special reference to Q.s. al-Baqara/2: 106 and al-Hajj/22: 52 as a case study.